A Role for Galanin N-Terminal Fragment (1–15) in Anxiety- and Depression-Related Behaviors in Rats. - Millón-Peñuela, Carmelo; Flores-Burgess, Antonio; Narváez-Peláez, Manuel; Borroto Escuela, Dasiel Óscar; Santín-Núñez, Luis Javier; Parrado-Romero, Concepción; Narvaez, Jose Angel; Fuxe, Kjell; Díaz-Cabiale, Zaida (Oxford Academic, 2015)
Galanin (GAL) plays a role in mood regulation. In this study we analyzed the action of the active N-terminal fragment [GAL(1–15)] in anxiety- and depression-related behavioral tests in rats. Methods: The effect of GAL(1–15) was analyzed in the forced swimming test, tail suspension test, open field test, and light/dark test. The proximity of GAL1 and GAL2 receptors was examined with the proximity ligation assay (PLA). We tested the GAL receptors involved in GAL(1–15) effects with the GAL2 receptor antagonist M871 and with an in vivo model of siRNA GAL2 receptor knockdown or siRNA GAL1 receptor knockdown rats. The effects of GAL(1–15) were also studied in the cell line RN33B. Results: GAL(1–15) induced strong depression-like and anxiogenic-like effects in all the tests. These effects were stronger than the ones induced by GAL. The involvement of the GAL2 receptor was demonstrated with M871 and with the siRNA GAL2 receptor knockdown rats. The PLA indicated the possible existence of GAL1 and GAL2 heteroreceptor complexes in the dorsal hippocampus and especially in the dorsal raphe nucleus. In the siRNA GAL1 receptor knockdown rats the behavioral actions of GAL(1–15) disappeared, and in the siRNA GAL2 receptor knockdown rats the reductions of the behavioral actions of GAL(1–15) was linked to a disappearance of PLA. In the cell line RN33B, GAL(1–15) decreased 5-HT immunoreactivity more strongly than GAL. Conclusions: Our results indicate that GAL(1–15) exerts strong depression-related and anxiogenic-like effects and may give the basis for the development of drugs targeting GAL1 and GAL2 heteroreceptor complexes in the raphe-limbic system for the treatment of depression and anxiety.
Keywords: Depresión mental; Angustia; Neuropéptidos; Galanin; Depression; Anxiety